N3 Subclassification Incorporated into the Final Pathologic Staging of Gastric Cancer: A Modified System Based on Current AJCC Staging. Issue 8 (February 2015) - Yeh, Chun-Nan; Wang, Shang-Yu; Hsu, Jun-Te; Chiang, Kun-Chun; Cheng, Chi-Tung; Tsai, Chun-Yi; Liu, Yu-Yin; Liao, Chien-Hung; Liu, Keng-Hao; Yeh, Ta-Sen
Abstract : Abstract: The seventh edition of the American Joint Committee on Cancer (AJCC) TNM classification system for gastric cancer (GC) was established in 2009. We assessed the unmet medical needs of patients with the N3 classification of the seventh TNM staging system by comparing survival according to the extent of nodal involvement, with a particular focus on the cutoff points for the number of involved nodes in the N3 classification. We retrospectively reviewed 3178 patients with GC who were registered in the GC database of the Department of General Surgery at the Chang Gung Memorial Hospital between 1994 and 2010. Among them, 884 patients undergoing curative intent resection had N3 lymph node involvement. The clinicopathological features and surgical outcomes were compared among all patients with GC and between the N3a and N3b groups. N3b might impose GC patients with poor clinical outcome. We proposed a modified staging system, based on AJCC seventh edition, accordingly. T1-3N3 might be not simply categorized into stage IIIA as seventh AJCC suggested. Taking N3a and N3b into consideration, T1-3N3 might be further categorized into stage IIIB and IIIC, respectively, as we proposed, based on survival analysis. In addition, T4bN3bM0 is as dismal as M1 disease. In our proposed staging system, good discriminations between different stages are still maintained. The N3 category should be subclassified as N3a or N3b due to the survival differences. Furthermore, T1-3N3aM0 could be categorized as stage IIIB, T1-3N3bM0 could be categorized as stage IIIC, T4aN3bM0 could be categorized as stage IIID, and T4bN3bM0 might be regarded as stage IV as we proposed. Abstract : Supplemental Digital Content is available in the text